Évaluation des méthodes de classifications dirigées (spectrale et orientée objet) sur les images satellitaires à THRS - Patrice N’guessan Akoguhi; Hyppolite N’da Dibi; Marc Houin Godo; Germain Miessan Adja; Fernand Koffi Kouamé (VertigO)
This study aims to analyze the performance of spectral classifications and object oriented classification, for mapping of the urban area of Cocody and Attécoubé. To achieve our aim, a satellite image at very high spatial resolution (VHSR) was used. For this work, these two methods of classifications were successively applied to three test sites, namely a well-built area, an area with poor housing and an undeveloped area. The results of two treatments are compared to analyze performances. It appears from these treatments that object-oriented classification is better suited than the spectral approach for mapping sites built because it improves the mapping accuracy of 4,58%. At sites with poor housing, the two classifications show almost similar comprehensive details. Thus, the spectral classification provides an improvement of 0,73% compared to the object-oriented approach. On undeveloped land, the spectral classification is best shown with an overall improvement of 8.22% compared to the object-oriented approach. In short, the object-oriented classification seems appropriate for the extraction of units of well-structured sites. When the level of organization of the site decreases, the performance of the object oriented classification fall in favour of the spectral classification.urbanization, spectral classification, object-oriented classification, remote sensing, Côte d’Ivoire